(untitled) (Research, Society and Development, 2022)
Managing projects for success requires a mix of competencies, whether interpersonal, technical, cognitive, and these competencies may explain variations in project performance. In this context, it is challenging to determine the relative importance of change agent competencies for each project management approach. This article aims to present the relative importance of ten competencies of change agents in relation to project management approaches. Through an online questionnaire with change agents, followed by a fuzzy Topsis multicriteria analysis, was identified the degree of belonging of each competence to each project management approach. We identified that team management and project management competencies are essential in the respondent’s opinion when using predictive approaches, while leadership and technical competencies are essential for hybrid approaches. For the agile approach, communication skills, flexibility, social skills, problem-solving skills, reliability and professionalism, conflict management and technical competencies were considered essential.